ACHPA: A sensor based system for automatic environmental control in hydroponics - SIDDIQ,Asif (2020)
Abstract The trend towards tunnel farming and hydroponic systems is increasing owing to the climatic changes as well as the need to increase crop yield. Hydroponic is a technique of growing plants without soil. Tunnel farming and hydroponic system requires controlled environmental parameters like temperature, humidity and soil moisture for better production of crops. This paper presents an effective method, named, ACHPA (Automatically Controlled Hydro-Ponic Agriculture) scheme that monitor and controls environmental parameters using sensors and controller. ACHPA provides better environmental control over traditional manual monitoring and controlling, thus yield high-quality crops. Sensor based monitoring and control system regulates the temperature and humidity of the tunnel to yield better. For the sake of saving water, an efficient method of drip irrigation is implemented which delivers water directly to the plants rather than being sprayed on as in conventional farming method. The proposed system here is tested for controlled environment and observations recorded for crop analysis purpose. This makes an effective solution to growing highly efficient, good quality and disease free crop production.